Igualdad de oportunidades: una aplicación al sistema tributario chileno - ejecutivo, editor (Estudios de Economía, 2016)
This work evaluates the fiscal distributive policy (tax and transfer payments) of Chile at the perspective of the Equality of Opportunities approach. Under this criterion it is desirable to compensate people by the circumstances in that they are born but it is necessary to allow the differences originated in the individual effort. The main conclusion is that the, in the Chilean case, the application of the equality of opportunities approach on the fiscal system leads to lower the income marginal taxes rate and the worsening of the income distribution.